In Search Of A Christian Public Theology In The Indonesian Context Today - Joas Adiprasetya (DISKURSUS - JURNAL FILSAFAT DAN TEOLOGI STF DRIYARKARA, 2013)
Abstract: This article deals with the contemporary task of Christian public theology in constructing a contextual model that is able to maintain the dialectic of commonality and particularity. Such a model must pay attention to the search for common ground among many cultural-religious identities, while at the same time it must respect those identities in their own paticularities. The sensitivity to and solidarity with the victims of the New Order’s’ regime must also be fundamental elements of such a model. To do so, this article discusses two competing theories in social philosophy (liberalism and communitarianism), and their parallel theories in theology (revisionism and post-liberalism). The necessity to construct a more balanced third way between those theories is needed, if Indonesian Christians want to be open to their social and political call and faithful to their Christian distinctiveness. Keywords: Public theology, liberalism, communitarianism, revisionism, post-liberalism, commonality, particularity. Abstrak: Artikel ini membahas tugas kontemporer teologi publik Kristen dalam mengkonstruksi sebuah model kontekstual yang mampu mempertahankan dialektika kesamaan dan kekhususan. Model semacam ini haruslah memperhatikan usaha menemukan dasar bersama di antara banyak identitas kultural-religius, sekaligus pada saat bersamaan menghargai identitas-identitas tersebut di dalam keunikan mereka masing-masing. Kepekaan dan solidaritas pada para korban di bawah rejim Order Baru di masa silam harus menjadi unsur-unsur mendasar bagi model semacam itu. Artikel ini mendiskusikan dua teori yang saling bersaing di dalam filsafat sosial (liberalisme dan komunitarianisme), dan teori-teori sejajar di dalam teologi (revisionisme dan pascaliberalisme). Tuntutan untuk mengkonstruksi sebuah jalan ketiga yang lebih seimbang antara teori-teori tersebut sungguh dibutuhkan, jika orang-orang Kristen Indonesia ingin berbuka pada panggilan sosial dan politis mereka sembari tetap setia pada keunikan Kristiani mereka. Kata-kata Kunci: Teologi publik, liberalisme, komunitarianisme, revisionisme, pascaliberalisme, komunalitas, partikularitas.